2019
DOI: 10.21500/20112084.3753
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Graded Response Model to a Scale of Empathic Behavior

Abstract: The results obtained from the application of the Graded Response Model (GRM) to the items of the Scale of Empathic Behavior whose authors are Auné, Abal and Attorresi (2017) are presented. The sample was obtained by accessibility and consisted of Argentine university students (80% Women). None of the items presented uniform or non-uniform gender differential item functioning. The GRM assumptions of local independence and unidimensionality were successfully corroborated. Threshold parameters tended to be locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…El primero espera que todos los ítems representen al θ que está midiendo; el segundo, que no debe existir varianza irrelevante compartida entre los ítems, dado que, si existen pares de ítems localmente dependientes, puede existir otra dimensión (sustantiva o no); y el último, el DIF, se asocia con la evaluación de la invarianza de medición, es decir, que la ausencia de DIF implicaría que el θ se mide de forma distinta entre los grupos (e.g. Auné, Abal, & Attorresi, 2019). Actualmente, existen modelos que permiten romper con alguno de estos supuestos, por ejemplo, los modelos multidimensionales de la TRI (e.g.…”
Section: Aplicación De La Teoría De La Respuesta Al íTem (Tri)unclassified
“…El primero espera que todos los ítems representen al θ que está midiendo; el segundo, que no debe existir varianza irrelevante compartida entre los ítems, dado que, si existen pares de ítems localmente dependientes, puede existir otra dimensión (sustantiva o no); y el último, el DIF, se asocia con la evaluación de la invarianza de medición, es decir, que la ausencia de DIF implicaría que el θ se mide de forma distinta entre los grupos (e.g. Auné, Abal, & Attorresi, 2019). Actualmente, existen modelos que permiten romper con alguno de estos supuestos, por ejemplo, los modelos multidimensionales de la TRI (e.g.…”
Section: Aplicación De La Teoría De La Respuesta Al íTem (Tri)unclassified
“…The graded response model (GRM) developed by Samejima [45] is applied in the analysis of data collected from a Likert-type attitude scale. The model runs in a two-step process; the first step estimates the probability of a certain skill that an individual has chosen from the given scale by the following equation, as adopted from Aune et al [46]:…”
Section: Graded Response Model (Grm)mentioning
confidence: 99%
“…On the other hand, it has been suggested that IRT is derived from CTT, and that the latter is a very simple form of IRT. The widespread use of IRT models in Latin America is relatively recent and still limited in scope ( 40 ). However, the relationships between IRT and CTT are very useful for a better understanding of both approaches and to facilitate future well-informed applications ( 41 ).…”
Section: Introductionmentioning
confidence: 99%